Magnesium biomaterials for orthopedic application: A review from a biological perspective. Issue 6 (24th January 2014) - Walker, Jemimah; Shadanbaz, Shaylin; Woodfield, Timothy B. F.; Staiger, Mark P.; Dias, George J.
Abstract Magnesium (Mg) has a long history of investigation as a degradable biomaterial. Physicians first began using Mg for biomedical applications in the late 19th century. Experimentation continued with varying levels of success until the mid‐20th century when interest in the metal waned. In recent years the field of Mg‐based biomaterials has once again become popular, likely due to advancements in technology allowing improved control of corrosion. Although this has led to success in vascular applications, continued difficulties in predicting and controlling the corrosion rate of Mg in an intraosseous environment has impeded the development of Mg‐based biomaterials for orthopedic applications. In this review, an initial summary of the basic properties and the physiological role of Mg are followed by a discussion of the physical characteristics of the metal which lend it to use as a degradable biomaterial. A description of the historical and modern applications for Mg in the medical field is followed by a discussion of the methods used to control and assess Mg corrosion, with an emphasis on alloying. The second part of this review concentrates on the methods used to assess the corrosion and biocompatibility of Mg‐based orthopedic biomaterials. This review provides a summary of Mg as a biomaterial from a biological perspective. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1316–1331, 2014.